2013
DOI: 10.1108/00368791311311169
|View full text |Cite
|
Sign up to set email alerts
|

Wear behaviour of aluminium/alumina/graphite hybrid metal matrix composites using Taguchi's techniques

Abstract: Purpose -Recent advances in modern technology have generated the need to develop newer materials for better antifriction and wear properties. The objective is to analyse the significance of design parameters that significantly affects the dry sliding wear. Design/methodology/approach -The tribological behaviour of aluminium alloy (Al-Si10Mg) reinforced with alumina and graphite produced by liquid metallurgy is studied using pin-on-disc wear test apparatus under dry sliding condition. Experiments are conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 22 publications
5
30
0
Order By: Relevance
“…Results from References [18][19][20] indicate that the alumina particle content can have a positive influence on the tribological behaviour of the ZA27 alloy-based hybrid composite.…”
Section: Introductionmentioning
confidence: 99%
“…Results from References [18][19][20] indicate that the alumina particle content can have a positive influence on the tribological behaviour of the ZA27 alloy-based hybrid composite.…”
Section: Introductionmentioning
confidence: 99%
“…L16 orthogonal array was selected for the present investigation and the degree of freedom for the orthogonal array should be greater than or equal to, the sum of the variables [21]. The parameters and the corresponding levels are shown in Table 2.…”
Section: Plan Of Experimentsmentioning
confidence: 99%
“…They revealed that the volume fraction of reinforcement was the most decisive parameter on wear rate. Radhika et al [10] investigated the wear and frictional behaviour of Al/alumina/ graphite hybrid MMCs and understood that graphite as primary reinforcement increases the wear resistance of the produced composites and sliding distance was the most predominant factor on the output responses. Ramakoteswara Rao et al [11] performed the dry sliding wear and friction behaviour of AA7075 filled with TiC particulates composites and reported that the wear rate and COF decreased with increases the weight percentage of TiC content.…”
Section: Introductionmentioning
confidence: 99%
“…Since it is very simple and inexpensive method, flexibility and homogeneous dispersion of ceramic particles can be achieved by mechanical stirring action [7]. Some literatures reported that the effect of different variables on tribological characteristics of AMCs [8][9][10][11][12][13][14][15][16][17][18]. Baskaran et al [8] studied the effects of wear control parameters like reinforcement, load, sliding velocity and sliding distance on wear rate.…”
Section: Introductionmentioning
confidence: 99%